2021
DOI: 10.1139/as-2020-0024
|View full text |Cite
|
Sign up to set email alerts
|

Sea ice and snow phenology in the Canadian Arctic Archipelago from 1997 to 2018

Abstract: The multiple islands and narrow channels that form the Canadian Arctic Archipelago (CAA) complicate snow/ice monitoring, as coarse resolution satellite observations are unable to resolve smaller-scale changes in snow/ice cover. We present the first study showing the utility of the Interactive Multisensor Snow and Ice Mapping System (IMS) 24 km (1997–2018) and 4 km (2004–2018) products to investigate changes in sea ice and snow phenology together in the CAA. While ice break-up and snow retreat are shifting earl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 83 publications
(112 reference statements)
1
10
0
Order By: Relevance
“…Examining snow and ice cover at the pan-Arctic scale provides important information on how the cryosphere is responding to climate change as a whole, however the large degree of spatial variability warrants further investigation into snow and ice conditions at regional scales. For example, Dauginis and Brown (2020) demonstrate that the CAA is responding differently to warming compared to other regions of the Arctic; their findings show later summer clearing of ice and earlier sea ice freeze and snow onset since 2004, in line with findings from previous studies that showed no significant trends toward earlier sea ice melt onset dates in the CAA (e.g. Mahmud et al 2016;Marshall et al 2019).…”
Section: Trends and Correlationssupporting
confidence: 74%
See 3 more Smart Citations
“…Examining snow and ice cover at the pan-Arctic scale provides important information on how the cryosphere is responding to climate change as a whole, however the large degree of spatial variability warrants further investigation into snow and ice conditions at regional scales. For example, Dauginis and Brown (2020) demonstrate that the CAA is responding differently to warming compared to other regions of the Arctic; their findings show later summer clearing of ice and earlier sea ice freeze and snow onset since 2004, in line with findings from previous studies that showed no significant trends toward earlier sea ice melt onset dates in the CAA (e.g. Mahmud et al 2016;Marshall et al 2019).…”
Section: Trends and Correlationssupporting
confidence: 74%
“…). Regions of later WCIS are also evident, for example the Eastern Parry Channel (Dauginis andBrown, 2020). The surrounding area(Cornwallis Island, Bathurst Island, and Northern Somerset Island) shows significant clustering between the sea ice and snow trends (no lakes are large enough to be detected at 4 km resolution in this region) (Figure6c, d), further highlighting this local region of later ice/snow-off.…”
mentioning
confidence: 82%
See 2 more Smart Citations
“…The Canadian Arctic Archipelago (CAA), however, has been shown to exhibit earlier freeze trends during recent years (e.g. Dauginis and Brown, 2020) and weaker trends toward earlier melt onset compared to other Arctic regions (e.g. Mahmud et al 2016;Marshall et al 2019).…”
Section: Introductionmentioning
confidence: 99%